2013
DOI: 10.1016/j.aam.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

q-Hook length formulas for signed labeled forests

Abstract: A signed labeled forest is defined as a (plane) forest labeled by {1, 2, . . . , n} along with minus signs associated to some vertices. Signed labeled forests can be viewed as an extension of signed permutations. We define the inversion number, the flag major index and the R-major index on signed labeled forests. They can be considered as type B analogues of the indices for labeled forests introduced by Björner and Wachs. The flag major index for signed labeled forests is based on the flag major index on signe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We will use W B (F ) and W D (F ) to denote the set of all signed labelings and the set of all even-signed labelings of a forest F , respectively. The type B and type D analogues of the inversion number of a labeled forest introduced by Björner and Wachs [2] was proposed by Chen et al [4]. The definition is as follows.…”
Section: Inversions and Bottom-to-top Maximamentioning
confidence: 99%
See 3 more Smart Citations
“…We will use W B (F ) and W D (F ) to denote the set of all signed labelings and the set of all even-signed labelings of a forest F , respectively. The type B and type D analogues of the inversion number of a labeled forest introduced by Björner and Wachs [2] was proposed by Chen et al [4]. The definition is as follows.…”
Section: Inversions and Bottom-to-top Maximamentioning
confidence: 99%
“…Note that if a signed labeling w is in fact in W(F ), then inv B (F, w) = inv(F, w). Chen et al [4] showed that for a forest F with n vertices w∈W B (F )…”
Section: Inversions and Bottom-to-top Maximamentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, Seo [26] developed a bijection between these two combinatorial classes. Other combinatorial works on hook length formulae include: [2,25,12,7,14,30,5,29,15,6,9,18]. Kuba and Panholzer [19] discovered a general identity of hook length series in the form of a recurrence relation on the coefficients of the hook length series.…”
Section: Introductionmentioning
confidence: 99%